Screen viewing time and externalising problems in pre-school children in Northern Thailand - Supakanya Tansriratanawong (2018)
© 2017 NISC Pty Ltd. Objectives: There are increasing reports of younger children accessing media and screen. This study aims to describe screen use in pre-school children and its association with externalising problems. Methods: A cross-sectional study of pre-schoolers aged two to five years was conducted. Their caregivers were asked to provide data regarding screen use by their children and themselves. The Child Behaviour Checklist (CBCL) was completed by caregivers to assess their child’s behaviour. Results: Participants included 200 caregivers of pre-school children. There were 47% of pre-schoolers who had used at least three types of media. When comparing the 0–1, >1 to 2, and >2 hours per day of screen viewing time groups, the children who had experienced more screen time also had significantly more background media and their caregivers had more screen time (p < 0.001). The externalising problem scores increased with more screen viewing time, although the relationship was not statistically significant. However, age and gender of the child were factors associated with externalising problems from the multiple linear regression analysis (p = 0.03). Conclusion: Pre-schoolers with more screen viewing time did not have a significantly greater externalising problem score than those with less screen time. A longitudinal study with a larger sample size would provide more information.